Strategic and Innovative Areas in the Development of National Migration Policy in the Context of Macroeconomic Growth of the Ukrainian Economy - T. BULAKH; S. ZALYUBOVSKA; G. KASHCHEІEVА (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The distinctive features of the Ukrainian migration policy today are inadequate administrative, legal and social regulation of migration processes, creating bureaucratic barriers in public administration bodies. These problems call for solutions that would promote consolidation of democracy and observation of human rights in Ukraine, its integration in the global community, on the one hand, and enhancement of the national security, on the other. Being subject to broad-scale political debate in scientific and political circles of Ukraine, the migration problem needs continuing research.The article analyzes performance and trends in the migration policy of Ukraine. Its features and efficiency are revealed.It was found that the main characteristics of the country’s external migration are: dominance of labor migrants among the migrant categories; by gender structure, labor migration is most common among men. The main destinations of labor migration are Poland, Slovakia, Czech Republic, Hungary.The main characteristics of internal migration are the continuation of the trend towards urbanization, with the decreasing rural population and increasing urban population. High migration losses of the population are characteristic of the Western and South-Western regions of Ukraine. Most people changed their place of residence for Kharkiv, Kyiv and Dnipropetrovsk regions.It was found that the migration policy of Ukraine is characterized by low efficiency. At the moment, migration processes are spontaneous. And this leads to an increase in the disproportion of regional labor markets, increasing social tensions, the formation of conditions for the spread of ideas of national intolerance among the Ukrainian population.The main reasons behind the growing migration activity in Ukraine are highlighted: the instability of the socio-economic environment, decreasing salary rate, overall welfare and quality of life.Measures to improve the migration policy of Ukraine are proposed.